The Canadian yearbook of international law : Annuaire canadien de droit international. Tome XL. (Canadian yearbook of international law, 2003)
Since its advent in 1961, The Canadian Yearbook of International Law has had three main objectives: to make available to Canadians and the international community a systematic presentation of the best Canadian thought on problems of international law; to promote the development of Canadian research on international law; and to make available documents and commentaries that reveal the practice of Canadian institutions in matters of international law. UBC Press is honoured to have been involved with this venerable project, and is proud to celebrate the publication of its fortieth volume this ye.